Exploring cultural representation through tourism-related cultural words translation on Hangzhou Tourism Website - Chen, Shiyue; Shahila Mansor, Nor; Mooisan, Chin; Redzuan Abdullah, Muhammad Alif (Sciedu Press, 2023)
This study investigates the translation procedures of the translated cultural words on the tourism website and explores whether the cultural representation is author-oriented or reader-oriented. A descriptive qualitative research method was used in this study. Hangzhou tourism website is selected as the case. 160 cultural words were collected and extracted from the website in total. The results indicated that retention, calque, and paraphrase were widely used translation procedures, and cultural representation was author-oriented and tended to preserve the source culture. This study adds new knowledge to the existing Chinese-English online tourism translation studies and enhances the quality of tourism translation.